2017
DOI: 10.1177/0300060517692483
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin improves the healing process of thermally-induced skin damage in rats

Abstract: ObjectiveTo evaluate the effect of the phenolic compound naringenin on thermal burn-induced inflammatory responses and oxidative stress in rats.MethodsFirst degree thermal burn injuries were induced in shaved rats by 10 s immersion of the back surface in water at 90℃. Naringenin treatment (25, 50 and 100 mg/kg/day) was initiated 24 h following burn injury, and continued for 7 days. On treatment day 7, serum tumour necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, nitric oxide (NO), prostaglandin (PG)E2, casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…MCH and MCHC are major Data are mean±SE of n=6; ψ ATD versus control at p≤0.05, ф ATD versus control at p≤0.01, * ATD+Therapy versus ATD at p≤0.05, * * ATD+Therapy versus ATD at p≤0.01, § Significant at 5% for ANOVA: Data are mean±SE of n=6; ψ ATD versus control at p≤0.05, ф ATD versus control at p≤0.01, * ATD+Therapy versus ATD at p≤0.05, * * ATD+Therapy versus ATD at p≤0.01, § blood parameters. Naringenin capable to increase the platelet count as previously reported that they have wound healing properties [21].…”
Section: Resultsmentioning
confidence: 64%
“…MCH and MCHC are major Data are mean±SE of n=6; ψ ATD versus control at p≤0.05, ф ATD versus control at p≤0.01, * ATD+Therapy versus ATD at p≤0.05, * * ATD+Therapy versus ATD at p≤0.01, § Significant at 5% for ANOVA: Data are mean±SE of n=6; ψ ATD versus control at p≤0.05, ф ATD versus control at p≤0.01, * ATD+Therapy versus ATD at p≤0.05, * * ATD+Therapy versus ATD at p≤0.01, § blood parameters. Naringenin capable to increase the platelet count as previously reported that they have wound healing properties [21].…”
Section: Resultsmentioning
confidence: 64%
“…In continuation of the previous discussion, we would like to emphasize that the topical application of NAR stimulates anti-inflammatory and antioxidant effects, thereby known to show significant increase in wound contraction [ 59 ]. Reported antioxidant and angiogenic roles of NAR also potentiate healing of wounds through restraining endothelial apoptosis through growth factor and inflammatory mediator modulation [ 60 ].…”
Section: Resultsmentioning
confidence: 81%
“…Further work is needed to elucidate the protection mechanism. Naringenin, extensively contained in lemons, oranges, and grapes, is reported to be a potent active of attenuating skin inflammation and oncogenesis [ 4 , 40 ]. Kaempferol has been demonstrated to restrain photoaging and UV-induced carcinogenesis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%